Lymphovascular Space Invasion Portends Poor Prognosis in Low-Risk Endometrial Cancer. Issue 7 (September 2015) - dos Reis, Ricardo; Burzawa, Jennifer K.; Tsunoda, Audrey T.; Hosaka, Masayoshi; Frumovitz, Michael; Westin, Shannon N.; Munsell, Mark F.; Ramirez, Pedro T.
<x xml:space="preserve">Abstract</x> Objective The prognostic significance of lymphovascular space invasion (LVSI) in patients with early-stage endometrial cancer is not established. We sought to determine if LVSI status in patients with early-stage low-risk endometrial cancer correlates with recurrence and survival. Methods The records of all women who underwent hysterectomy for primary treatment of endometrial cancer from January 2006 through January 2011 at 1 academic institution were reviewed. Patients with grade 1 or 2 endometrioid histology, myometrial invasion less than 50%, and disease confined to the uterus (clinical International Federation of Obstetrics and Gynecology stage IA) were analyzed. Fisher exact test and the Wilcoxon rank-sum test were applied to compare patients with and without LVSI. Recurrence-free survival (RFS) and overall survival (OS) were calculated using the Kaplan-Meier method. Results Two hundred forty patients met the inclusion criteria. Forty (16.7%) had LVSI. Ninety-one patients (37.9%) underwent lymphadenectomy. Median tumor size was 30 mm in patients with and 26 mm in patients without LVSI (P = 0.150). Thirty patients (12.5%) received adjuvant therapy. Site of recurrence did not differ between patients with and without LVSI. Patients with LVSI were more likely to have myometrial invasion (P < 0.001), postoperative pathologic grade 2 disease (P < 0.001), to undergo lymphadenectomy (P = 0.049) and receive adjuvant therapy (P < 0.001). The 5-year cumulative incidence of recurrence was 3.8% in the no-LVSI group and 14.2% in the LVSI group (P = 0.053). The presence of LVSI was significantly associated with worse RFS (P = 0.002) and OS (P = 0.013). Conclusions Patients with low-risk endometrial cancer and LVSI have worse RFS and OS despite being more likely to undergo lymphadenectomy and adjuvant therapy.